The Determinants of Fast Fashion Consumption Among Generation-Z Muslim Consumers in Indonesia - Resfa Fitri; Devina D. Kusumaningrum; M. Iqbal Irfany (SMART Insight, 2025)
This study explores the characteristics and key determinants influencing fast fashion consumption among Generation Z Muslim consumers, focusing on factors such as FOMO, fashion trends, and religious values. Using a descriptive and logistic regression approach, a questionnaire with 40 questions was distributed to 200 Generation Z participants across five Indonesian provinces. Logistic regression analysis identified age, gender, FOMO (Fear of Missing Out), fashion trends, price, product design, and product quality as significant factors influencing purchasing decisions. Education, income, religiosity, and E-WOM (Electronic Word of Mouth) were not significant. This research is unique in examining variables such as religiosity, fashion trends, and Generation Z Muslims in relation to fast fashion purchasing, using logistic regression for analysis. Fast fashion producers who prioritize design, quality, and affordability to meet Gen Z preferences can achieve business success in Indonesia, where this generation dominates the population.